MODERN CONCEPTS OF NECROTIZING ENTEROCOLITIS IN NEWBORNS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Relevance. Necrotizing enterocolitis (NEC) remains one of the most serious causes of morbidity and mortality among premature infants. Despite the progress in neonatology, the incidence of NEC ranges from 1% to 7%, and mortality reaches 20-30%, increasing to 40-60% with surgical intervention. Premature infants with extremely low body weight (